ASM Pacific Technology Limited - Tang, Hung Kei (2013)
This case traces the corporate history and development of ASM Pacific Technology Limited (ASMPT), a public-listed "technology" firm in Hong Kong. The company was founded in 1975 as a two-man outfit that sold encapsulation equipment from the Netherlands and materials from the US. In 1998, the firm was developing and mass-manufacturing its own award-winning semiconductor products, and had spun-off operations in China and Singapore.